Spontaneous left main coronary artery dissection complicated by pseudoaneurysm formation in pregnancy: role of CT coronary angiography - Rahman, Shahid (BioMed Central, 2009)
We report a case of a 26-year-old female, who presented at 34 weeks of an uncomplicated pregnancy with an acute ST elevation anterior wall myocardial infarction. Cardiac catheterization suggested a left main coronary artery dissection with pseudoaneurysm formation. The patient's course was complicated by congestive heart failure. She was initially managed conservatively by a multidisciplinary team including heart failure specialists, obstetricians, and cardiovascular surgeons. 4 days after admission, her LMC was imaged by dual-source 64 slice Cardiac computed tomography, coronary dissection was identified extending to the lumen, and the presence of pseudoaneurysm was confirmed. She underwent subsequently a staged procedure, which included placement of an intra-aortic balloon pump, cesarean section, and coronary artery bypass grafting. This case illustrates the utility of coronary artery CT imaging to assess the complexity and stability of coronary artery dissections, thereby helping to determine the need for, and timing of revascularization procedures.